General synthesis of core–shell FeAlOx nanosphere-based nanoreactors with enhanced catalytic performance - Zhao, Shun; Liu, Pei; Li, Ping; Xi, Jiangbo; Wen, Liangsong; Wang, Shuai (Nanoscale, 2025)
Rationally designing and fabricating high-performance core–shell nanostructures for catalytic organic synthesis is significant yet challenging. Here, we report a solvothermal/calcination strategy to prepare novel core–shell iron–aluminum oxide (FeAlOx) nanosphere-based nanoreactors incorporating active heterometals (AHM = Pd, Cu, or Mn). Leveraging the synergistic benefits of their unique core–shell structure, high specific surface area (178 m2 g−1), and well-dispersed heterometallic active sites, AHM/FeAlOx nanoreactors (e.g., Pd/FeAlOx, Cu/FeAlOx, Mn/FeAlOx) demonstrate outstanding catalytic performance in organic reactions such as 4-nitrophenol reduction, 2,4-dinitroaniline reduction, and benzyl alcohol selective oxidation. Notably, the Pd/FeAlOx nanoreactor achieves an unprecedented average turnover frequency of 165.8 min−1 in 4-nitrophenol reduction, 8-fold higher than those of benchmark metal oxide-supported catalysts (typically 0.01–20.4 min−1), while maintaining over 95% activity after 11 catalytic cycles. These findings establish a versatile platform for rational design principles and scalable synthesis protocols for FeAlOx-based nanoreactors, enabling their tailored implementation in advanced organic synthesis through architecturally controlled confinement catalysis.